The Influence Of Affective Commitment And Psychological Empowerment On Turnover Intention Of Millennial Workers - Muchtadin (ORGANIZE: Journal of Economics, Management and Finance, 2023)
Turnover Intention needs attention because it can have a negative impact on an organization. This research aims to determine the magnitude of the impact that affective commitment and psychological empowerment have on millennial worker turnover. The respondents were 100 millennial workers. Sampling was carried out using convenience sampling. Data analysis process with SEM PLS. The research results found that affective commitment has a negative effect on turnover of millennial workers. Interestingly, psychological empowerment actually has a positive effect on turnover among millennial workers. Future researchers can use moderating variables on the influence of psychological empowerment on turnover intention. This research contributes to efforts to reduce turnover of millennial workers through affective commitment and psychological empowerment.